2018
DOI: 10.5194/acp-2018-920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of two different biogenic emission models on modelled ozone and aerosol concentrations in Europe

Abstract: <p><strong>Abstract.</strong> Biogenic volatile organic compound (BVOC) emissions are one of the essential inputs for chemical transport models (CTMs), but their estimates are associated with large uncertainties leading to significant influences on air quality modelling. This study aims at investigating the effects of using different BVOC emission models on the performance of a CTM in simulating secondary pollutants, i.e. ozone, organic and inorganic aerosols. The Euro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Emissions models have been shown to perform well in both the unstressed and severe drought phases (e.g. Emmerson et al, ; Guenther et al, ; Jiang et al, ) but underestimate observed concentrations during the mild‐to‐moderate drought phase (Potosnak et al, ; Seco et al, ). Conceptual models (Niinemets, ; Potosnak et al, ) have been developed to explain the impacts of mild droughts on isoprene emissions but these have not been tested until now.…”
Section: Discussionmentioning
confidence: 99%
“…Emissions models have been shown to perform well in both the unstressed and severe drought phases (e.g. Emmerson et al, ; Guenther et al, ; Jiang et al, ) but underestimate observed concentrations during the mild‐to‐moderate drought phase (Potosnak et al, ; Seco et al, ). Conceptual models (Niinemets, ; Potosnak et al, ) have been developed to explain the impacts of mild droughts on isoprene emissions but these have not been tested until now.…”
Section: Discussionmentioning
confidence: 99%
“…Under the current rate of CO 2 increase, such high concentration is predicted for the year 2065 according to the most pessimistic RCP8.5 scenario (Meinshausen et al, ), whereas 400 ppm were reached in the year 2015 (Blunden & Arndt, ). Such a dramatic CO 2 ‐driven reduction of isoprene emission from plants might have relevant effects on tropospheric chemistry because isoprene has been shown to significantly affect the concentration of tropospheric ozone and other oxidants (Jiang et al, ), and perhaps also the capacity to adapt to climate change (Lerdau, ; Loreto et al, ). However, it was shown that most of the negative effect of elevated CO 2 on isoprene is lost under a simultaneous increase of temperature (Sharkey & Monson, ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of isoprene emission models have been developed (Andreani‐Aksoyoglu & Keller, 1995; Arneth et al, 2011; Grote & Niinemets, 2008; Guenther et al, 2012, 2006; Müller et al, 2008; Pierce & Waldruff, 1991), with the resulting emission estimates varying by up to a factor of 3 for the same region and season (Guenther et al, 2006; Jiang et al, 2019; Lathière et al, 2010). As isoprene emissions are concurrently influenced by many environmental variables, field measurements as well as studies in controlled environments are necessary to validate emission models.…”
Section: Introductionmentioning
confidence: 99%